2013
DOI: 10.1016/j.jpeds.2013.06.055
|View full text |Cite
|
Sign up to set email alerts
|

A Year-Long Caregiver Training Program Improves Cognition in Preschool Ugandan Children with Human Immunodeficiency Virus

Abstract: Objective To evaluate if mediational intervention for sensitizing caregivers (MISC) MISC biweekly caregiver training significantly enhanced child development, compared with biweekly training on health and nutrition (active control) and to evaluate whether MISC training improved the emotional well-being of the caregivers compared with controls. Study design Sixty of 120 rural Ugandan preschool child/caregiver dyads with HIV were assigned by randomized clusters to biweekly MISC training alternating between hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 29 publications
7
64
1
Order By: Relevance
“…It is likely that central nervous system HIV infection in children results in frontostriatal dysfunction (Adam et al, 2003). Consistent with other studies, children with HIV infection in our study tended to score lowest in verbal, memory, and quantitative scales compared to their uninfected peers, though it is not statistically significant (Baillieu & Potterton, 2008;Boivin et al, 2013;Levenson, Mellins, Zawadzki, Kairam, & Stein, 1992;Sherr et al, 2009;Van et al, 2008). Two studies (Bisiacchi, Suppiej, & Laverda, 2000;Koekkoek et al, 2008) reported executive function deficits as the most sensitive cognitive measure in relation to HIV disease progression.…”
Section: Discussionsupporting
confidence: 88%
“…It is likely that central nervous system HIV infection in children results in frontostriatal dysfunction (Adam et al, 2003). Consistent with other studies, children with HIV infection in our study tended to score lowest in verbal, memory, and quantitative scales compared to their uninfected peers, though it is not statistically significant (Baillieu & Potterton, 2008;Boivin et al, 2013;Levenson, Mellins, Zawadzki, Kairam, & Stein, 1992;Sherr et al, 2009;Van et al, 2008). Two studies (Bisiacchi, Suppiej, & Laverda, 2000;Koekkoek et al, 2008) reported executive function deficits as the most sensitive cognitive measure in relation to HIV disease progression.…”
Section: Discussionsupporting
confidence: 88%
“…This secondary analysis utilizes baseline data from 288 HIV-infected women participating in a randomized controlled trial testing the Meditational Intervention for Sensitizing Caregivers (MISC), a one-year program aimed at enhancing child physical and neuropsychological development (Boivin et al, 2013). Details of the parent study are described elsewhere (Bass, Nakasujja, Familiar-Lopez, Sikorskii, Murray,…& Boivin, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…33 It has been previously used by our group in pediatric HIV research in Uganda. 35,36 Although the CBCL can provide a wide array of DSM-V and Syndrome scale scores, our principal outcomes were Internalizing, Externalizing, and Total symptoms.…”
Section: Assessments For Neuropsychological Outcomesmentioning
confidence: 99%